Enoxaparin for the prevention of preeclampsia and intrauterine growth restriction in women with a prior history – an open-label randomised trial (the EPPI trial): study protocol. Issue 1 (December 2016) - Groom, K.; McCowan, L.; Stone, P.; Chamley, L.; McLintock, C.
Abstract Background Preeclampsia and intrauterine fetal growth restriction (IUGR) are two of the most common causes of maternal and perinatal morbidity and mortality. Current methods of predicting those at most risk of these conditions remain relatively poor, and in clinical practice past obstetric history remains the most commonly used tool. Aspirin and, in women at risk of preeclampsia only, calcium have been demonstrated to have a modest effect on risk reduction. Several observational studies and randomised trials suggest that low molecular weight heparin (LMWH) therapy may confer some benefit. Methods/design This is a multicentre open label randomised controlled trial to determine the effect of the LMWH, enoxaparin, on the prevention of recurrence of preeclampsia and/or IUGR in women at high risk due to their past obstetric history in addition to standard high risk care for all participants. Inclusion criteria: A singleton pregnancy >6+0 and <16+0 weeks gestation with most recent prior pregnancy with duration >12 weeks having; (1) preeclampsia delivered <36+0 weeks, (2) Small for gestational age (SGA) infant <10th customised birthweight centile delivered <36+0 weeks or, (3) SGA infant ≤3rd customised birthweight centile delivered at any gestation. Randomisation is stratified for maternal thrombophilia status and women are randomly assigned to 'standard high risk care' or 'standard high risk care' plus enoxaparin 40 mg from recruitment until 36+0 weeks or delivery, whichever occurs sooner. Standard high risk care includes the use of aspirin 100 mg daily and calcium 1000–1500 mg daily (unless only had previous SGA with no preeclampsia). The primary outcome is preeclampsia and/or SGA <5th customised birthweight centile. Analysis will be by intention to treat. Discussion The EPPI trial has more focussed and clinically relevant inclusion criteria than other randomised trials with a more restricted composite primary outcome. The inclusion of standard use of aspirin (and calcium) for all participants will help to ensure that any differences observed in outcome are likely to be related to enoxaparin use. These data will make a significant contribution to future meta-analyses and systematic reviews on the use of LMWH for the prevention of placental mediated conditions. Trial registration ACTRN12609000699268 Australian New Zealand Clinical Trials Registry. Date registered 13/Aug/2009 (prospective registration).